Effects of Ca:Mg ratio and pH on soil chemical, physical and microbiological properties and grass N yield in drained peat soil. Issue 1 (2nd January 2023) - Deru, Joachim G. C.; Hoekstra, Nyncke; van Agtmaal, Maaike; Bloem, Jaap; de Goede, Ron; Brussaard, Lijbert; van Eekeren, Nick
ABSTRACT: In three dairy grasslands on peat, minerals were added to manipulate the soil Ca:Mg ratio with or without effect on pH. The responses of soil properties and grass N yield were measured. CaCO3 application led to higher soil Ca:Mg ratio and pHKCl compared to the untreated control, decreased Ntotal and Ctotal, and increased P availability. Grass N yield increased in the first year by only 6% of the reduction in soil Ntotal, but not in the second year. A higher pH increased SOM decomposition, especially in soils with high P availability. MgCO3 reduced the Ca:Mg ratio, had little influence on soil parameters and no effect on grass N yield. In contrast, CaSO4 and MgSO4 did not influence pHKCl but reduced grass N yield in most cases. Results suggest stabilisation of organic matter by Ca binding in treatments with added Ca. We conclude that grass N yield was not linked with changes in Ca:Mg ratio but with soil pH. The pH effects on SOM decomposition depended on P availability and Ca binding. Hence, to avoid potentially large soil losses of C and N, the current agricultural advice on pH management in peat grasslands should be better adapted to local edaphic characteristics.